Between the mind and the senses: Jean Mitry’s approach to cinematic consciousness: Toward an idea of the virtual image in the cinema (I) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
Representing altered states of consciousness, even through the most phantasmal of technical images, is an inherent contradiction; once we attribute a physical body, i.e. objectivity, to mental images, we deny what Husserl considers their very essence. Jean Mitry draws from this assumption when discussing filmic access to mental states from a phenomenological perspective. The following essay reconsiders Mitry’s contribution with specific reference to the role of projection, technically and metaphorically speaking, in the cinematic technique and imagination; this, with the intention of suggesting some crucial questions for the comparison between the filmic forms of the visible and those inaugurated by the technology of the virtual.
Keywords: Mitry; Husserl; Mental state; Projection; Imagination